Development of smart bed prototype - Norfadhilah Hasan; Salmiza Said; Nurul Ashikin Ismail (Southeast Asian Journal of Technology and Science, 2020)
Nowadays, almost every household has several alarm clock devices. Many people choose their morning wake up routine with all-in-one devices because of the freedom offered by today's technology like mobile phone or other portable clock. However, the issue of overslept still arises in our community.  This is due to the fact that the current alarm clock is simple to disarm and also have a snooze button that will make the user possible to sleep again. Therefore, this Smart Bed prototype is designed to overcome problems of overslept. Furthermore, this project also can help those with hearing impairments where they can’t hear the alarm sound. The main objective of this project is to design a prototype of Smart Bed to help people who have problems waking up at the designated time. This prototype uses Arduino as the processor part. This project includes the alarm itself and also connected to the vibrator and the water sprinkler circuit. The vibration in the bed and then sprinkle of the water will cause the user to feel uncomfortable to sleep and get them to wake up.